BREAKING BARRIERS: THE ROLE OF GENDER SENSITIZATION IN PROMOTING EQUALITY AT INSTITUTIONS AND WORK PLACES BREAKING - Razia Abdullah; Showkat Hussain Dar (RADJA PUBLIKA, 2026)
Gender sensitization is a crucial process in fostering a society that values equality, respect, and inclusivity. It involves developing awareness and understanding of gender roles, stereotypes, and biases that perpetuate discrimination and inequality. By challenging traditional norms and promoting progressive attitudes, gender sensitization helps create an environment where individuals, regardless of gender, have equal opportunities and rights. This paper explores the significance of gender sensitization in various spheres, including education, workplaces, policymaking, and social interactions. It highlights the impact of ingrained biases and how sensitization initiatives, such as gender training programs, inclusive education, and media representation, contribute to breaking societal barriers. Furthermore, the paper examines the role of governments, organizations, and communities in implementing policies and interventions that address gender disparities and promote equitable treatment for all. Through an analytical lens, the study underscores the need for a holistic approach to gender sensitization, encompassing awareness campaigns, curriculum reforms, and behavioural changes at individual and institutional levels. Ultimately, fostering a gender-sensitive society is essential for achieving sustainable development, social harmony, and human rights for all. This research emphasizes that gender sensitization is not merely an academic or policy-driven concept but a transformative process that empowers individuals and communities to embrace diversity and inclusion.